2010
DOI: 10.1021/ol902958m
|View full text |Cite
|
Sign up to set email alerts
|

C3-Symmetric Chiral Trisimidazoline: Design and Application to Organocatalyst

Abstract: C(3)-symmetric chiral trisimidazoline was designed and synthesized as a new entry of organocatalyst with the concept of constructing C(3)-symmetric molecules with three C(2)-symmetric chiral components, and the application of this novel catalyst to asymmetric conjugate addition of beta-ketoesters to nitroolefins was described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…5 In this context, we have recently reported a C 3 -symmetric chiral trisimidazoline 3 as a new entry of organocatalyst. 6,7 We evaluated monoimidazoline 1, bisimidazoline 2, and trisimidazoline 3 as Brønsted base catalysts 8 for the enantioselective conjugate addition of a-substituted b-ketoesters to nitroolefins and found that C 3 -symmetric chiral trisimidazoline 3 was the most effective ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…5 In this context, we have recently reported a C 3 -symmetric chiral trisimidazoline 3 as a new entry of organocatalyst. 6,7 We evaluated monoimidazoline 1, bisimidazoline 2, and trisimidazoline 3 as Brønsted base catalysts 8 for the enantioselective conjugate addition of a-substituted b-ketoesters to nitroolefins and found that C 3 -symmetric chiral trisimidazoline 3 was the most effective ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H and 13 C NMR spectra of 5 were consistent with those previously reported for the enantiomer (S,S)-5. 11 In addition, specific rotation of the resulting product 5 has roughly the same magnitude as (S,S)-5, and we determined that (R,R)-5 was provided without loss of stereochemistry under the applied reaction conditions. 8…”
Section: Tablementioning
confidence: 74%
“…3, 133.1, 132.5, 128.5, 127.7, 127.5, 126.4, 126.0, 125.6, 124.6, 69.0, 64.5, 64.0, 30.0, 19.2, 19.0;IR 3381, 3055, 2959, 2928, 2874, 1508, 1466, 1387, 1368, 1076, 1047 4.2.3. (R, ,2-ethanediamine (3c 5, 139.0, 126.6, 124.9, 68.6, 63.9, 63.7, 34.2, 31.1, 29.9, 19.2, 19.0;IR 3399, 3310, 2963, 2876, 1508, 1464, 1362, 1074, 1022 6.91-6.96 (m, 8H), 3.89 (s,2H),3.74 (dd,J=3.6,11.4 Hz,2H),3.67 (dd,J=7.4,11. 2, 136.3, 129.0, 126.9, 68.6, 64.3, 63.9, 29.9, 20.9, 19.2, 19.0;IR 3360, 3312, 2959, 2926, 2874, 1653, 1514, 1464, 1076 6. 4H),4H),3.86 (s,2H),3.75 (dd,J=3.6,11.4 Hz,2H),3.68 (dd,J=7.4,11.4 Hz),3.71 (s) 2, 134.4, 128.0, 113.6, 68.3, 64.1, 63.7, 54.9, 29.8, 19.2, 18.9;IR 3383, 3302, 2963, 2874, 1611, ...…”
Section: J=6mentioning
confidence: 99%
“…[4,12] To our delight, tripodal imidazolidine-pyridine L6 showed the best catalyst activity for the simple benzoylation reaction and gave the product with 62 % ee ( Table 1, Entry 9 vs. Entries 2 and 5).…”
Section: Resultsmentioning
confidence: 94%